Mapping productivity zones for Indian mustard in Haryana: A comprehensive analysis of climatic and physical influences: MAPPING PRODUCTIVITY ZONES FOR MUSTARD IN HARYANA : A COMPREHENSIVE ANALYSIS - SHIVJEET KAUR; MANDEEP YADAV (Journal of Oilseeds Research, 2024)
This study aims to conceptualize the productivity zoning of Indian mustard in Haryana by analyzing winter season temperature, rainfall, soil characteristics, and crop area and production. Data for this study was sourced from Chaudhary Charan Singh Haryana Agricultural University (CCS HAU), Hisar. The analysis identified that the western, southern, and central regions of Haryana exhibit favourable physio-climatic conditions for mustard cultivation, while the north-eastern districts are less suitable. A winter isotherm of 18°C and isohyets of 50 mm significantly influenced the mustard-growing areas. Despite increasing rainfall, the lower temperatures in the north-eastern districts likely limit mustard productivity in those areas. Hisar and Rewari emerged as the most suitable districts due to their optimal soil and climatic conditions. The study highlights that the decreasing temperature stowards the north-eastern districts, despite higher rainfall, adversely affect mustard productivity. This research provides valuable insights for agricultural planning and policy formulation, aiming to enhance mustard crop yield in Haryana by identifying regions with optimal conditions and addressing the limitations in less suitable areas. These findings are crucial for improving mustard cultivation strategies and ensuring better resource allocation to maximize productivity in the state.